Inequalities in HIV testing uptake and needs among men who have sex with men living in Ireland: findings from an internet survey. Issue 2 (20th November 2018) - O'Donnell, K; Fitzgerald, M; Quinlan, M; Hickson, F; Keogh, P; Schmidt, AJ; McCartney, D; Barrett, P; O'Dea, S; Igoe, D
Abstract : Objectives: HIV disproportionately affects men who have sex with men (MSM) in Ireland. The aim of this study was to improve understanding of HIV testing among MSM living in Ireland to inform prevention and testing initiatives. Methods: We used data from the MSM Internet Survey Ireland 2015 (MISI 2015), a cross‐sectional survey of MSM living in Ireland. We identified factors associated with never having tested for HIV using univariable and multivariable logistic regression. We identified preferred sites for future tests and examined the relationships between unmet HIV testing needs and socio‐demographic groups. Results: More than one‐third ( n = 1006; 36%) of MSM had never tested for HIV. Multivariable logistic regression showed that untested men were more likely to be aged 18–24 years, live outside Dublin, have a lower level of education, be born in Ireland, identify as bisexual, be out to fewer people, and not have had sex with a man in the previous 12 months. The same groups of men also had the least knowledge about HIV and were least confident in accessing an HIV test. Men who had never tested for HIV were more likely to prefer testing by their general practitioner (GP) or using home sampling HIV kits and less likely to prefer testing in a sexual health clinic. Conclusions: HIV prevention and testing programmes for MSM should be targeted towards younger men, those living outside Dublin and those with lower levels of education. We recommend increased promotion and availability of free HIV testing services in a range of clinical and nonclinical settings (including self‐sampling and home testing).